2015
DOI: 10.1016/j.heares.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Audibility, speech perception and processing of temporal cues in ribbon synaptic disorders due to OTOF mutations

Abstract: Mutations in the OTOF gene encoding otoferlin result in a disrupted function of the ribbon synapses with an impaired multivesicular glutamate release. Most affected subjects present with congenital hearing loss and abnormal auditory brainstem potentials associated with preserved cochlear hair cell activities (otoacoustic emissions, cochlear microphonics [CMs]). Transtympanic electrocochleography (ECochG) has recently been proposed for defining the details of potentials arising in both the cochlea and auditory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 62 publications
1
56
0
Order By: Relevance
“…One showed favourable speech perception performance 3 years after implantation; the other's speech perception performance was mediocre. Santarelli et al performed disyllabic recognition testing in six ANSD patients with biallelic OTOF mutations and reported that all six patients attained speech perception scores of 90%‐100% at 1‐1.5 year after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One showed favourable speech perception performance 3 years after implantation; the other's speech perception performance was mediocre. Santarelli et al performed disyllabic recognition testing in six ANSD patients with biallelic OTOF mutations and reported that all six patients attained speech perception scores of 90%‐100% at 1‐1.5 year after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that genetic testing is of great help in determining the site of pathology in paediatric sensorineural hearing impairment (SNHI) . Specifically, mutations in the OTOF gene, a common cause of clinical ANSD, are an indicator that the pathology is confined to the synapse; post‐synaptic neurons and nerve fibres are preserved for electrical stimulation of CI. In this study, we retrospectively analysed CI outcomes in 10 patients with OTOF mutations to explore the utility of genetic diagnosis to help determine the timing of cochlear implantation in patients with ANSD.…”
Section: Introductionmentioning
confidence: 99%
“…We are only beginning to obtain insight into the protein structure of ferlins 55,56 . To date, approximately 90 pathogenic mutations of OTOF have been reported; the majority of these muta tions are assumed to be nonsense or truncation mutations that cause inactivation of otoferlin 57 , result ing in DFNB9type hearing impairment. Otoferlin knockout mice are likely to be an appropriate animal model for DFNB9 (REFS 19,30).…”
Section: Genetic Auditory Synaptopathiesmentioning
confidence: 99%
“…The term of "auditory neuropathy" was then proposed to initially describe hereditary sensorimotor neuropathies [8]. Later, several authors suggested the more comprehensive term of "auditory neuropathy/auditory dys-synchrony" (AN/AD) or "auditory neuropathies" to underline the loss of temporal coding due to an abnormal synchronization at different levels of the peripheral neural pathways [7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%